Analisis Efisiensi Kinerja Kelompok Bank Menurut Modal Inti - Nugroho, Muchammad Rio; Ladi Wajuba Perdini Fisabilillah (Jurnal Ekonomika : INDEPENDEN, 2025)
This study aims to analyze the performance efficiency of banks categorized under Core Capital Group 1 (KBMI 1) during the 2020–2023 period. Efficiency is measured using the Data Envelopment Analysis (DEA) method through an intermediation approach, where the input variables used are the Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), and Loan to Deposit Ratio (LDR), while the output variables include the amount of loans disbursed and operating income. The results indicate that the efficiency of banks with the smallest core capital is dynamic. Bank Victoria International (BVIC) achieved full efficiency throughout the study period, while Bank IBK Indonesia (AGRS) and Bank Amar Indonesia (AMAR) consistently experienced inefficiency. Other factors influencing bank efficiency include macroeconomic conditions and the readiness for banking digitalization. Banks that are able to adapt to digital transformation tend to operate more efficiently.